Comparing Inpatient Complication Rates between Octogenarians and Nonagenarians Following Primary and Revision Total Hip Arthroplasty in a Nationally Representative Sample 2010–2014 - Evan M Dugdale (Geriatrics, 2019)
We compared inpatient postoperative complication rates between octogenarians and nonagenarians undergoing primary and revision total hip arthroplasty (THA). We used inpatient admission data from 2010−2014 from the Nationwide Inpatient Sample (NIS). We compared the rates at which nonagenarians and octogenarians developed each complication in the inpatient setting following both primary THA (PTHA) and revision THA (RTHA). A total of 40,944 inpatient admissions were included in our study which extrapolates to a national estimate of 199,793 patients. A total of 185,799 (93%) were octogenarians and 13,994 (7%) were nonagenarians. PTHA was performed on 155,669 (78%) and RTHA was performed on 44,124 (22%) of the patients. Nonagenarians undergoing PTHA required transfusions significantly more frequently (33.13% v. 24.0%, p < 0.001) and developed urinary tract infection (5.14% v. 3.92%, p = 0.012) and acute kidney injury (5.50% v. 3.57%, p < 0.001) significantly more frequently than octogenarians. Nonagenarians undergoing RTHA required transfusions significantly more frequently (51.43% v. 41.46%, p < 0.001) and developed urinary tract infection (19.66% v. 11.73%, p < 0.001), acute kidney injury (13.8% v. 9.66%, p < 0.001), pulmonary embolism (1.24% v. 0.67%, p = 0.031), postoperative infection (1.89% v. 1.11%, p = 0.023), sepsis (3.59% v. 2.43%, p = 0.021) and other postoperative shock (1.76% v. 1.06%, p = 0.036) significantly more frequently than octogenarians. Nonagenarians undergoing RTHA also had a significantly higher inpatient mortality rate (3.28% v. 1.43%, p < 0.001) than octogenarians. Orthopedic surgeons and primary care providers can use these findings to help counsel both their octogenarian and nonagenarian patients preoperatively when considering THA. Our analysis can help these patients better understand expected inpatient complication rates and assist them in deciding whether to pursue surgical intervention when applicable.